VD_FINDINFO Jug / 2020 / 399 vom 26. August 2020 - VD Tribunal cantonal (2020)
ATTÉNUATION DE LA PEINE, FIXATION DE LA PEINE, PRINCIPE DE LA CÉLÉRITÉ, DÉCISION DE RENVOI | 47 CP, 392 CPP (CH), 5 CPP (CH)